1985
DOI: 10.1007/bf02744054
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence of alkali halides doped with alkaline earth impurities

Abstract: Doping with alkaline earth impurities converts the alkali halides into very efficient phosphors. LiF doped with Mg is extensively used in radiation dosimetry. However, the phenomenon of thermoluminescence in these materials is far from dear. LiF-TLD 100 is artificially separated from the rest of the alkali halide phosphors. The available experimental data are not fully utilised in building a model for thermoluminescence processes. In this review, thermoluminescence properties of LiF-TLD 100 and other alkali ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 228 publications
(194 reference statements)
0
5
0
Order By: Relevance
“…Division of Radiological Protection, Bhabha Atomic Research Centre, Bombay 400 085, India *Department of Physics, Nagpur University, Nagpur 400 010, India MS received 31 March 1986;revised 12 May 1986 In this note we elaborate some points on LiF mentioned in the review article on "Thermoluminescence of alkali halides doped ~vith alkaline earth impurities" by Deshmukh and Moharil (1985), hereafter referred to as paper I.…”
Section: Thermoluminescence Of Alkali Halides Doped With Alkaline Earmentioning
confidence: 99%
“…Division of Radiological Protection, Bhabha Atomic Research Centre, Bombay 400 085, India *Department of Physics, Nagpur University, Nagpur 400 010, India MS received 31 March 1986;revised 12 May 1986 In this note we elaborate some points on LiF mentioned in the review article on "Thermoluminescence of alkali halides doped ~vith alkaline earth impurities" by Deshmukh and Moharil (1985), hereafter referred to as paper I.…”
Section: Thermoluminescence Of Alkali Halides Doped With Alkaline Earmentioning
confidence: 99%
“…TL studies in a number of alkali halides have been reported by Deshmukh and Moharil [3]. These studies do not, however, yield detailed information about the structure of the traps involved.…”
Section: Introductionmentioning
confidence: 98%
“…The electrons situated in traps do not lose energy to drop to the lower available states. There have been numerous studies which characterize the electron traps and their applications in dosimetry [3], but the nature and the physical structure of such traps even in an alkali halide is not yet fully established.…”
Section: Introductionmentioning
confidence: 99%
“…Two prominent peaks were observed by these workers but no explanation is provided about the structure of corresponding traps. Further, TL studies are available in a number of alkali halides (Deshmukh and Moharil, 1985) without any specific information about the structure of traps.…”
Section: Introductionmentioning
confidence: 99%